2008
DOI: 10.1074/jbc.m706784200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Uncoupling Protein-2 Mediates Steatotic Liver Injury following Ischemia/Reperfusion

Abstract: Steatotic livers are not used for transplantation because they have a reduced tolerance for ischemic events with reduced ATP levels and greater levels of cellular necrosis, which ultimately result in total organ failure. Mitochondrial uncoupling protein-2 (UCP2) is highly expressed in steatotic livers and may be responsible for liver sensitivity to ischemia through mitochondrial and ATP regulation. To test this hypothesis, experiments were conducted in lean and steatotic (ob/ob), wild-type, and UCP2 knock-out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 41 publications
(48 reference statements)
9
69
0
Order By: Relevance
“…Previous studies suggested that UCP2 promotes mitochondrial proton leak and increases susceptibility of liver to ischemia/reperfusion injury. 27,39 However, the underlying mechanisms of how UCP2 sensitizes hepatocytes to death are not fully understood. Our data for the first time suggest the possible mechanism of how the compromised energy metabolism signals the core apoptotic machinery (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that UCP2 promotes mitochondrial proton leak and increases susceptibility of liver to ischemia/reperfusion injury. 27,39 However, the underlying mechanisms of how UCP2 sensitizes hepatocytes to death are not fully understood. Our data for the first time suggest the possible mechanism of how the compromised energy metabolism signals the core apoptotic machinery (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…23 An interesting note is that UCP2 expression becomes significantly abundant in hepatocytes of fatty liver, steatotic liver, and chronic liver disease conditions. [24][25][26] Under these conditions, hepatocytes are prone to ischemia/reperfusion-induced liver injury, 27 implying that UCP2 has pathogenic roles in the development of liver diseases. It was found that UCP2 expression induced by obesity in hepatocytes promotes liver ATP depletion.…”
mentioning
confidence: 99%
“…28 After 45 minutes of hepatic ischemia, surviving mice were sacrificed at 6, 12, or 24 hours after reperfusion.…”
Section: Hepatic Warm Iri and Complement Depletion In Micementioning
confidence: 99%
“…At 8 wk of age, following dietary treatment, wt lean, wt fat feed, C3 Ϫ/Ϫ lean, and C3 Ϫ/Ϫ fat feed mice were subjected to total warm hepatic ischemia as previously described (21). Ischemia was performed for 45 min and surviving mice were sacrificed 24 h after reperfusion.…”
Section: Surgical Modelsmentioning
confidence: 99%
“…H&E staining of liver sections was performed as previously described (21). Sections stained with H&E were graded in a blinded fashion for centrilobular necrosis on a 0 -3 scale as described by Neil and Hubscher.…”
Section: Histologymentioning
confidence: 99%